APLIKASI NOTIFIKASI JADWAL KULIAH BAGI MAHASISWA UNIVERSITAS ISLAM LAMONGAN BERBASIS ANDROID - Siti Mujilawati (Joutica, 2017)
The use of fast and sophisticated technology will make the solution for academics. Lamongan Islamic University (UNISLA) is a private university located in the heart of Lamongan. As a competitive private university, one of them on the use of technology then UNISLA must be able to change and create a manual technology into all-digital technology. One of them is the use of smartphones as a medium of communication and information media. With the support of Informatics engineering program, UNISLA is able to create lecture schedule applications android based. Application that has been made has a feature that the most important is the notification of each user (student). Students will have their respective account as login and setting up the schedule that has been provided by the system according to the student's college schedule, then the system will provide reminder in the form of notification as well as the alarm on each student.